Dynamical Analysis of DTNN with Impulsive Effect - Chao Chen; Zhenkun Huang; Honghua Bin; Xiaohui Liu (Discrete Dynamics in Nature and Society)
We present dynamical analysis of discrete-time delayed neural networks with impulsive effect. Under impulsive effect, we derive some new criteria for the invariance and attractivity of discrete-time neural networks by using decomposition approach and delay difference inequalities. Our results improve or extend the existing ones.